2012
DOI: 10.1088/0953-8984/24/42/424205
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dispersion interactions on the hydrogen adsorption properties of expanded graphite

Abstract: We demonstrate the importance of London dispersion forces in defining the adsorption capacity within expanded graphite, a simple model of the more complex experimental geometries of activated carbon, using a combination of the non-local correlation functional of Dion et al paired with a recent exchange functional of Cooper (vdW-DF(C09x)) and a classical continuum model. Our results indicate that longer ranged interactions due to dispersion forces increase the volume over which molecules interact with a porous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 36 publications
5
35
0
Order By: Relevance
“…At the same time, H 2 density in UMC mesopores is relatively low, close to the density of bulk gas, and undergoes only subtle changes with pressure. These findings were supported by theoretical calculations, using first-principle methods of treating the van der Waals interactions within density functional theory, which confirmed that H 2 density in subnanometer pores indeed could reach a liquidlike density even at 50 bar and 298 K [63,64]. The described SAS results demonstrate the advantage of adsorptive storage over compressed gas storage and emphasize the greater efficiency of micropores over mesopores in the adsorption process [65].…”
Section: Hydrogen Storage In Activated Carbonssupporting
confidence: 63%
“…At the same time, H 2 density in UMC mesopores is relatively low, close to the density of bulk gas, and undergoes only subtle changes with pressure. These findings were supported by theoretical calculations, using first-principle methods of treating the van der Waals interactions within density functional theory, which confirmed that H 2 density in subnanometer pores indeed could reach a liquidlike density even at 50 bar and 298 K [63,64]. The described SAS results demonstrate the advantage of adsorptive storage over compressed gas storage and emphasize the greater efficiency of micropores over mesopores in the adsorption process [65].…”
Section: Hydrogen Storage In Activated Carbonssupporting
confidence: 63%
“…We also tried to use some ab initio data for the H 2 -graphene interaction to obtain corresponding adsorption potential. However, as one can see in figure 7, different ILJ with ab initio data [36][37][38]. and semi-empirical potentials obtained via integration of H 2 − C pair potentials [39,40].…”
Section: Analysis Of the Results And Discussionmentioning
confidence: 97%
“…(For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.) i n t e r n a t i o n a l j o u r n a l o f h y d r o g e n e n e r g y x x x ( 2 0 1 5 ) 1 e1 0 nanoporous carbons and the expanded bilayer graphene with a series of the interlayer distances have already been reported with the similar strategy, but under the assumption that the fugacity coefficient is equal to unity or a empirical value [17,19,20]. It is of course not very precise.…”
Section: Prediction Of the Hydrogen Uptake Ratesmentioning
confidence: 93%
“…Obviously, the fugacity coefficients could be totally different, especially at low temperature. Although the empirical value for the hydrogen fluid in their work [19] seems to be close to the experiment, the old fitting process is not reliable. Thus, we conclude four points which should be considered: i).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation